Captain America, symbol of truth. Volume 2. Pax Mohannda - Onyebuchi, Tochi (Marvel Worldwide, Inc., 2023)
What is Sam willing to sacrifice for the mantle of Captain America? Still reeling from his conflict with Wakanda, Sam is called to the international stage once again to protect a visiting politician from the African nation of Mohannda. But the White Wolf has already put the second stage of his plan into motion, with dire consequences for both Sam's closest friends and Mohannda itself! When Sam's role as Captain America prevents him from pursuing his own justice, his government contact sets him up with a surprising new partner - an old ally long thought dead. It's the return of Steve Rogers' son, Ian, A.K.A. Nomad! But will Ian's return be a blessing or a curse? And what about Sam's previous partner, the Falcon? A heartbreaking showdown is in the offing.